Role of t-tubules in the control of trans-sarcolemmal ion flux and intracellular Ca2+ in a model of the rat cardiac ventricular myocyte - Pásek, Michal; Šimurda, Jiří; Orchard, C. H (European biophysics journal, 2012)
The t-tubules of mammalian ventricular myocytes are invaginations of the surface membrane that form a complex network within the cell, with restricted diffusion to the bulk extracellular space. The trans-sarcolemmal flux of many ions, including Ca(2+), occurs predominantly across the t-tubule membrane and thus into and out of this restricted diffusion space. It seems possible, therefore, that ion concentration changes may occur in the t-tubule lumen, which would alter ion flux across the t-tubule membrane. We have used a computer model of the ventricular myocyte, incorporating a t-tubule compartment and experimentally determined values for diffusion between the t-tubule lumen and bulk extracellular space, and ion fluxes across the t-tubule membrane, to investigate this possibility. The results show that influx and efflux of different ion species across the t-tubule membrane are similar, but not equal. Changes of ion concentration can therefore occur close to the t-tubular membrane, thereby altering trans-sarcolemmal ion flux and thus cell function, although such changes are reduced by diffusion to the bulk extracellular space. Slowing diffusion results in larger changes in luminal ion concentrations. These results provide a deeper understanding of the role of the t-tubules in normal cell function, and are a basis for understanding the changes that occur in heart failure as a result of changes in t-tubule structure and ion fluxes.
Keywords: Membrane Potentials; Calcium; Models, Cardiovascular; výpočetní biologie; Diffusion; vápník; Computer Simulation; difuze; Sarcolemma; modely kardiovaskulární; membránové potenciály; krysa rodu Rattus; kardiomyocyty; Animals; Sarcoplasmic Reticulum; zvířata; Rats; Myocytes, Cardiac; počítačová simulace; sarkolema; ionty; Ions; Computational Biology; sarkoplazmatické retikulum